Empowering Fish Cracker MSMEs through E-Branding and a Marketplace-Based Digital Catalog System to Improve Business Performance in Kuala Langsa - Alfian; Miftahul Zannah Sihombing; Ayu Prihatina; Cut tinur Jannah; Putri Nurfadhilla; Juli Dwina Puspita Sari; Nanda Safarida; Zefri Maulana; Safwandi; Safwan Kamal; Muhammad Amin; Khalda Hayatul Fazri Muna; Faisal Yahya; Dicky Armanda (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital transformation has become a key factor in enhancing the competitiveness of micro, small, and medium enterprises (MSMEs). However, many MSMEs in coastal areas still face challenges in strengthening their brand identity, presenting product information, and utilizing digital marketing channels. Similar challenges were identified among fish cracker MSMEs in Kuala Langsa, Langsa City, which still rely on conventional marketing practices, lack strong branding, and have not fully leveraged product catalogs and marketplaces. This community service program aimed to improve the understanding and readiness of MSME stakeholders to adapt to digital transformation by strengthening e-branding, introducing a digital catalog system, and enhancing literacy regarding the use of marketplaces. The program employed a Participatory Action Research (PAR) approach involving problem identification, action planning, socialization, mentoring, and reflection. Data were collected through observation, interviews, and documentation and analyzed using a qualitative descriptive approach. The results indicate an improvement in participants’ understanding of brand identity, the systematic presentation of product information, and the use of digital media as a marketing support tool. Furthermore, MSME actors demonstrated greater openness toward adopting technology for business development. This program provides an initial foundation for fish cracker MSMEs in Kuala Langsa to improve their readiness to adopt digital marketing gradually and sustainably in order to support more adaptive and competitive business development.